Relationship between kappa light chain level and demyelinating lesion localization in secondary progressive multiple sclerosis - İbrahim Acır; Esra Derya Dinç Polat; Hacı Ali Erdoğan; Elif Demir Eyüboğlu; Vildan Yayla (Alexandria Journal of Medicine)
Aim This study aims to investigate the intricate interplay between lesion localization and kappa light chain (KLC) levels in patients diagnosed with Secondary Progressive Multiple Sclerosis (SPMS), unraveling the underlying mechanisms contributing to lesion distribution and potential drivers of the observed relentless progression of neurological disability in SPMS.Material and Methods An observational study was conducted with a cohort of 23 SPMS patients meeting diagnostic criteria. Clinical, demographic data, and MRI scans were collected of 14 patients who had received any treatment in the past year. Serum KLC levels were measured, and statistical analyses were performed to identify correlations between age, KLC levels, and lesion distribution.Results The study revealed a significant positive correlation between age and the number of periventricular lesions, indicating a potential influence of aging processes on lesion distribution dynamics. Serum KLC levels showed a noteworthy positive correlation with the number of infratentorial lesions. However, no significant correlations were observed between Expanded Disability Status Scale (EDSS) scores and lesion counts.Conclusion The findings underscore the complex and multifaceted nature of SPMS pathogenesis. While age and serum KLC levels demonstrated associations with periventricular and infratentorial lesions, the lack of correlation between EDSS scores and lesion counts emphasizes the heterogeneous aspects of SPMS progression. These insights highlight the importance of a comprehensive understanding beyond lesion quantification to unravel the intricate mechanisms driving disability progression in SPMS.